Zinc Deficiency as Predictor of COVID-19 Severity: A Systematic Review and Meta-Analysis - Ayu Rizky Widowati; Sutrisno Sutrisno (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Despite the fact that zinc deficiency is asymptomatic, its incidence is rising over the world, with no visible clinical manifestation. Mineral and vitamin supplementation to prevent the inflammatory response is a major concern during the COVID-19 pandemic. Zinc may play a role in the development of a stronger immunological response. Nonetheless, there is insufficient information to investigate the benefits of zinc on its own. The impact of zinc deficiency on the severity of COVID-19 infection will be discussed in this systematic study. Material and Methods: We used the search phrases